The Credibility Problem in Unemployment Insurance Policy - Robert A.J. Dur (Tinbergen Institute, 1999)
If distortions in the labour market lead to inefficiently highunemployment, and policy makers cannot enter into a binding policy commitment before nominal wages are set, excessive inflation may result due to a credibility problem. This is the famous Kydland&Prescott - Barro&Gordon inflationary bias result. This paper shows that a similar credibility problem may exist in public unemployment insurance policy. I study a model inwhich trade unions, who set wages, interact with a policy maker, whodecides on the level of unemployment benefits and taxes. The policy maker is assumed to have the same preferences as the median voter, whose demand for unemployment benefits is driven by both insurance motives and ideological motives. If the policy maker cannot commit to future policies, and wages are relatively rigid, taxes and benefits are excessively high in equilibrium. Moreover, employment and hence output are inefficiently low in thediscretionary equilibrium. Akin to the case of monetary policy, I show that appointing a policy maker who is more conservative than the median voter may solve the credibility problem.
Keywords: D78; J51; 330; unemployment insurance policy; credibility problem; trade unions; Arbeitslosenversicherung; Glaubwürdigkeit; Theorie